2012
DOI: 10.1007/s00432-012-1353-5
|View full text |Cite
|
Sign up to set email alerts
|

Frequent epigenetic silencing of PCDH10 by methylation in human colorectal cancer

Abstract: Our results suggest that PCDH10 is an important tumor suppression gene with key roles of suppressing cell proliferation, clonogenicity, and inhibiting cell invasion in the development of colorectal cancer. Thus, PCDH10 methylation may constitute a useful biomarker of colorectal cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…PCDH10, a member of nonclustered protocadherin subfamily, was proposed as a tumor suppressor (6)(7)(8) in multiple cancers. Inactivation of PCDH10 because of promoter CpG hypermethylation has been detected in gastric, hepatocellular, colorectal, breast, cervical, lung, nasopharyngeal, esophageal, pancreatic, and bladder cancer (6,(9)(10)(11)(12)(13)(14)(15)(16). Functional studies revealed that re-expression of PCDH10 inhibits cell growth, reduces clonogenicity, restrains cell invasion, and induces cell apoptosis, substantiating its tumor suppressor roles (10,13,14,16).…”
Section: Introductionmentioning
confidence: 87%
“…PCDH10, a member of nonclustered protocadherin subfamily, was proposed as a tumor suppressor (6)(7)(8) in multiple cancers. Inactivation of PCDH10 because of promoter CpG hypermethylation has been detected in gastric, hepatocellular, colorectal, breast, cervical, lung, nasopharyngeal, esophageal, pancreatic, and bladder cancer (6,(9)(10)(11)(12)(13)(14)(15)(16). Functional studies revealed that re-expression of PCDH10 inhibits cell growth, reduces clonogenicity, restrains cell invasion, and induces cell apoptosis, substantiating its tumor suppressor roles (10,13,14,16).…”
Section: Introductionmentioning
confidence: 87%
“…The human PCDH10 gene is located at 4q28.3 and is involved as a tumor-suppressor gene. The promoter methylation and downregulation of PCDH10 gene expression has been demonstrated in various human cancer types including lymphoma, as well as gastric, prostate, bladder, colorectal and cervical cancer (9)(10)(11)(12). In previous studies, we found that PCDH10 is broadly expressed in normal adults, but almost undetectable in ΜΜ tissues and cell lines due to the promoter methylation of PCDH10.…”
Section: Introductionmentioning
confidence: 76%
“…The present study demonstrated that PCDH10 may suppress cell proliferation and invasion in colorectal cancer RKO cells. Flow cytometry analysis of PCDH10-re-expressed RKO cells revealed a significant decrease in the number of cells in the G2/M phase, and an increase in the number of cells in the G0/G1 phase, without inducing apoptosis (11). The ectopic expression of PCDH10 significantly reduced the colony formation efficiencies of the HCT116 cell line in monolayer culture and soft-agar assays in vitro (18) and suppressed tumorigenesis and liver metastasis in vivo, resulting in prolonged mice survival (36).…”
Section: Role Of Pcdh10 As a Functional Tsg In Crcmentioning
confidence: 98%
“…Previously, frequent epigenetic silencing of protocadherin 10 (PCDH10) was revealed in colorectal carcinogenesis. PCDH10 has been proposed to be a tumor suppressor gene involved in the processes of growth control, cell invasion and metastasis (11). The present study focuses on previous findings and aims to review the epigenetic alteration of PCDH10 and the possibility of PCDH10 methylation being a biomarker for CRC diagnosis.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation